Tackling the sustainability iceberg: a transaction cost economics approach to lower tier sustainability management - Meinlschmidt, Jan; Schleper, Martin C.; Foerstl, Kai (Emerald, 2018)
Purpose – This article investigates how buying firms manage their lower tier sustainability management (LTSM) in their supply networks and what contextual factors influence the choice of approaches. As most of the environmental and social burden is caused in lower tiers we use the iceberg analogy. Design/methodology/approach – Findings from 12 case studies and 53 interviews, publicly available and internal firm data are presented. In an abductive research approach, Transaction Cost Economics (TCE) conceptually guides the analytical iteration processes between theory and data. Findings – This study provides eight LTSM approaches grouped into three categories: direct (holistic, product-, region-, and event-specific) indirect (multiplier-, alliance-, and compliance-based) and neglect (tier-1-based). Focal firms choose between these approaches depending on the strength of observed contextual factors (stakeholder salience, structural supply network complexity, product and industry salience, past supply network incidents, socio-economic and cultural distance and lower tier supplier dependency), leading to perceived sustainability risk (PSR). Research limitations/implications – By depicting TCE’s theoretical boundaries in predicting LTSM governance modes, the theory is elevated to the supply network level of analysis. Future research should investigate LTSM at the purchasing category level of analysis to compare and contrast PSR profiles for different purchase tasks and to validate and extend the framework. Practical implications – This study serves as a blueprint for the development of firms’ LTSM capabilities that suit their unique PSR profiles. It offers knowledge regarding what factors influence these profiles and presents a model that links the effectiveness of different LTSM approaches to resource intensity. Originality/value – This study extends the application of TCE and adds empirically to the literature on multi-tier and sustainable supply chain management.